Three’s Company: discovery of a third syntype of Stegonotus lividus, a species of colubrid snake from Pulau Semau, Lesser Sunda Islands, Indonesia, with comments on an unpublished 19th Century manuscript by the naturalist Salomon Müller - Kaiser, Hinrich; Mecke, Sven; Kaiser, Christine M.; O’shea, Mark (Zootaxa, 2021)
We report on the discovery of a third, male specimen of Stegonotus lividus in the collection of the Muséum National d’Histoire Naturelle in Paris, France, and demonstrate that it is not only a member of the original type series but the only one of the three syntypes, whose morphology was detailed in the original description. We herein identify it as a paralectotype. In their description of S. lividus, Duméril et al. (1854) attributed authorship of the name to the German zoologist Salomon Müller, whose work was never published. By the rules of zoological nomenclature, author attribution solely via an unpublished manuscript is inadmissible, and the species is therefore properly listed as Stegonotus lividus (Duméril et al., 1854). The recent discovery of Müller’s handwritten manuscript, along with an unpublished drawing of one of these snakes by the Dutch artist Pieter van Oort, allows a better assessment of color and pattern for a species that remains known from only three preserved vouchers, as well as improved differentiation from other taxa occurring in the Lesser Sundas and Moluccas.